Detecção do Grapevine leafroll-associated virus 5 no Estado de São Paulo - Kuniyuki, Hugo; Rezende, Jorge Albeto Marques; Gaspar, José Osmar [UNESP]; Yuki, Valdir Atsushi (Grupo Paulista de Fitopatologia, 2008)
O enrolamento da folha da videira (grapevine leafroll) é uma doença atribuída a pelo menos nove vírus sorologicamente distintos, Grapevine leafroll-associated viruses 1 a 9 e designados GLRaV-1 a GLRaV-9. No Brasil, já é conhecida a existência do GLRaV-1, GLRaV-2, GLRaV-3 e GLRaV-6. Neste trabalho, foi demonstrada a ocorrência do GLRaV-5 em amostras de videiras cultivadas no Estado de São Paulo, mediante teste de Biotina-ELISA. O vírus foi detectado com baixa incidência nas cultivares avaliadas, exceto na 'Cardinal', que apresentou 100% de infecção. Este é o primeiro relato da ocorrência do GLRaV-5 no Brasil.

Grapevine leafroll is a complex disease that can be caused by any one of the nine serologically distinct closteroviruses, referred to as Grapevine leafroll-associated viruses 1 to 9 (GLRaV-1 to GLRaV-9). So far, it has been known the occurrence of GLRaV-1, GLRaV-2, GLRaV-3 and GLRaV-6 in Brazil. This work reports the identification of GLRaV-5 in leafroll-infected grape material from the State of São Paulo, by Biotine-ELISA. The virus was detected with low incidence in tested grape cultivars, except in 'Cardinal', which showed 100% infected. This is the first report of GLRaV-5 in Brazil.
Detection of Grapevine leafroll-associated virus 5 in the State of São Paulo, Brazil
Keywords: Vitis; Closteroviridae; GLRaV-5; Vitis; Closteroviridae; GLRaV-5